Scientific libraries in the classification of the state libraries - Čepanauskas, Algimantas (Knygotyra, 2024)
Typology and classification of libraries is the most actual problem in library science. A great number of specialists have made attempts to solve it; however, the problem remains unresolved. The article discusses the issues of special terminology related to library differentiation.The author focuses on new tendencies in the development of the state library system and the fact that modern library science requires a revision of existing classifications of libraries. The classification proposed by the author is based on the social functions of libraries.The proposed classification allows for outlining the role of scientific libraries within the library system of the USSR.
Keywords: -